Liposuction Practices among Brazilian Surgeons - Gustavo Moreira Costa de Souza; Sérgio Moreira da Costa; Márcio Henrique Lima Resende; Christiane Steponavicius Sobra; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: Since the 1980s, with Illouz, liposuction has gained popularity and represents one of the most commonly performed procedures in the world today. Some of the complications are serious and potentially lethal. Nevertheless, uniformity in its practice or the manner in which it is taught does not exist. Evaluating techniques employed by plastic surgeons may be the start toward standardization. Methods: A questionnaire on liposuction was given to plastic surgeons of different age groups and from regions of Brazil who were present at the 52nd Brazilian Conference for Plastic Surgery. Results: Two hundred forty-three questionnaires were filled out (n = 243). The average number of incisions was 9 (2-16). Two hundred forty-one surgeons (99%) made incisions along the anterior median/paramedian line, and 236 (97%) made incisions on the posterior median/paramedian line. Approximately half of those surveyed utilized general anesthesia. Two hundred nine surgeons (86%) placed the patient in the prone position during the procedure. One hundred forty-six (60%) interviewees performed superficial liposuction, with 22 (9%) performing liposuction only on this adipose layer. Eighty-five (35%) participants reported controlling the apparatus's pressure during the procedure. Conclusion: Liposuction procedures performed in Brazil have significant technical variations. This finding encourages us to reflect on the need to standardize liposuction practice and the manner in which it is taught so as to increase control over the procedure and its safety.